Krüppel-Like Factor 15 Modulates CXCL1/CXCR2 Signaling-Mediated Inflammatory Response Contributing to Angiotensin II-Induced Cardiac Remodeling - He, Shun; Lu, Yuanyuan; Guo, Yuetong; Li, Shijin; Lu, Xiao; Shao, Shuai; Zhou, Handan; Wang, Ruiqi; Wang, Jiguang; Gao, Pingjin; Li, Xiaodong (Frontiers in Cell and Developmental Biology, 2021)
Inflammation is involved in cardiac remodeling. In response to pathological stimuli, activated cardiac fibroblasts (CFs) secreting inflammatory cytokines and chemokines plays an important role in monocyte/macrophage recruitment. However, the precise mechanism of CFs-mediated inflammatory response participating in hypertension-induced cardiac remodeling remains unclear. In the present study, we investigated the role of transcription factor Krüppel-like factor 15 (KLF15) in this process. We found that KLF15 expression was decreased while chemokine CXCL1 and its receptor CXCR2 expression increased in the hearts of angiotensin II (Ang II)-infused mice. Compared to the wild-type mice, KLF15 knockout (KO) mice aggravated Ang II-induced cardiac hypertrophy and fibrosis. Deficiency of KLF15 promoted macrophage accumulation, increase of CXCL1 and CXCR2 expression, and mTOR, ERK1/2, NF-κB-p65 signaling activation in the hearts. Mechanistically, Ang II dose-dependently decreased KLF15 expression and CXCL1 secretion of cardiac fibroblasts but not cardiac myoblasts. Loss- or gain-of function studies showed that KLF15 negatively regulated CXCL1 expression through its transactivation domain. Intriguingly, adenovirus-mediated full length of KLF15 but not KLF15 with transactivation domain (TAD) deletion overexpression markedly prevented pathological change in Ang II-infused mice. Notably, administration of CXCR2 inhibitor SB265610 reversed KLF15 knockout-mediated aggravation of cardiac dysfunction, remodeling and inflammation induced by Ang II. In conclusion, our study identifies that KLF15 in cardiac fibroblasts negatively regulates CXCL1/CXCR2 axis-mediated inflammatory response and subsequent cardiac remodeling in hypertension.